DESAIN ARTISTIK PADA PUISI ”CATULLUS” DALAM BUKU PUISI-PUISI PILIHAN CATULLUS : (Kajian Teori Psikologi Sastra Coleridge) - Hartanu, Amir; Utami, Sri (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2024)
This research chose Catullus' poetry because it is interesting to study. Coleridge, in his psychological theory of literature, views artistic design as important. Because it will determine the color of literature, the creative process of a work (poetry), and reflect elements of a genius and free spirit. reading Catullus's poems to his lover Lesbia, it is clear that their relationship was tumultuous. His poems range from describing deep, passionate love to seething hatred. Catullus is the main character in the poem and is the author of the poem. This research uses a qualitative approach, namely content analysis as the method. The author uses a literary psychology approach to see the genius of writers in determining the beauty of poetry. This research falls into the realm of literary psychology, where literary psychology discusses more about psychological aspects, which include the psychology of the author or character in a literary work. The analysis technique used is based on qualitative data analysis methods, specifically collecting data through reading and paying special attention to the narrative text in the manuscript, presenting the data systematically and interpreting it based on literary psychological studies from the psychology researcher, namely Coleridge. This research will draw conclusions drawn from the data which will be explained in full.